Lactic Acid Bacteria (LAB) and Neuroprotection, What Is New? An Up-To-Date Systematic Review - Nurliana Abd Mutalib; Sharifah Aminah Syed Mohamad; Nor Atiqah Jusril; Nur Intan Hasbullah; Mohd Cairul Iqbal Mohd Amin; Nor Hadiani Ismail (MDPI AG, 2023)
Background: In recent years, the potential role of probiotics has become prominent in the discoveries of neurotherapy against neurodegenerative diseases, such as Alzheimer's and Parkinson's diseases. Lactic acid bacteria (LAB) exhibit neuroprotective properties and exert their effects via various mechanisms of actions. This review aimed to evaluate the effects of LAB on neuroprotection reported in the literature. Methods: A database search on Google Scholar, PubMed, and Science Direct revealed a total of 467 references, of which 25 were included in this review based on inclusion criteria which comprises 7 in vitro, 16 in vivo, and 2 clinical studies. Results: From the studies, LAB treatment alone or in probiotics formulations demonstrated significant neuroprotective activities. In animals and humans, LAB probiotics supplementation has improved memory and cognitive performance mainly via antioxidant and anti-inflammatory pathways. Conclusions: Despite promising findings, due to limited studies available in the literature, further studies still need to be explored regarding synergistic effects, efficacy, and optimum dosage of LAB oral bacteriotherapy as treatment or prevention against neurodegenerative diseases.